Phaeochromocytoma presenting with labile blood pressures following coronary artery bypass grafting. Issue 12 (3rd October 2016) - Roy, James; Akhunji, Zakir; Kushwaha, Virag; Mackie, James; Jepson, Nigel
Abstract: Pheochromocytomas have been reported prior to and during coronary artery bypass surgery. We present a patient with an undiagnosed pheochromocytoma who presented with labile hypertension following coronary artery bypass surgery. This case calls attention to the inclusion of an undiagnosed pheochromocytoma in the differential diagnosis for all patients who develop labile hypertension in the postoperative period following cardiac surgery.